Psychometric Properties of Speed Processing Ability Test: A Pilot Project - Fitri Andriani; Cholicul Hadi; Urip Purwono; Siti Sulasmi (Journal of Educational, Health and Community Psychology, 2019)
This study aims to examine the psychometric properties of a processing speed ability test constructed based on the Cattel-Horn-Carroll theory. According to Cattel-Horn-Carroll theory, processing speed ability is the ability that supports general intelligence. It has a significant effect on general intelligence (about 0.7). There are three narrow abilities of processing speed ability (i.e. perceptual speed, number facility and rate of test taking). 299 items of three narrow abilities were composed and trialed on 137 people. Data was analyzed using ITEMAN to select items and to estimate test reliability. Result shows that the tests under investigation have sufficient psychometric properties and adequate reliability.